Komposition-kurs über Sirius: Elektronische Musik und Trompete, Sopran, Baßklarinette, Baß (1975-77) - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2000)
Special facsimile edition printed for the composition seminar of the Stockhausen CoursesKuerten 2000 with sketches and explanations of SIRIUS
Keywords: 20th Century (1901-2000); Composing